Uncoupling growth and succinic acid production in an industrial Saccharomyces cerevisiae strain. Issue 4 (21st January 2021) - Liu, Yaya; Esen, Osman; Pronk, Jack T.; van Gulik, Walter M.
Abstract: This study explores the relation between biomass‐specific succinic acid (SA) production rate and specific growth rate of an engineered industrial strain of Saccharomyces cerevisiae, with the aim to investigate the extent to which growth and product formation can be uncoupled. Ammonium‐limited aerobic chemostat and retentostat cultures were grown at different specific growth rates under industrially relevant conditions, that is, at a culture pH of 3 and with sparging of a 1:1 CO2 –air mixture. Biomass‐specific SA production rates decreased asymptotically with decreasing growth rate. At near‐zero growth rates, the engineered strain maintained a stable biomass‐specific SA production rate for over 500 h, with a SA yield on glucose of 0.61 mol mol −1 . These results demonstrate that uncoupling of growth and SA production could indeed be achieved. A linear relation between the biomass‐specific SA production rate and glucose consumption rate indicated the coupling of SA production rate and the flux through primary metabolism. The low culture pH resulted in an increased death rate, which was lowest at near‐zero growth rates. Nevertheless, a significant amount of non‐viable biomass accumulated in the retentostat cultures, thus underlining the importance of improving low‐pH tolerance in further strain development for industrial SA production with S. cerevisiae . Abstract : Uncoupling of growth and product formation in industrial fermentation processes will minimize the formation of biomass as a by‐product and maximize the yield of product on substrate. In this work we provide a proof of principle of prolonged succinic acid production in an engineered, high producing, industrial strain of Saccharomyces cerevisiae at near‐zero growth rates.